THE INFLUENCE OF GENERAL PHYSICAL TRAINING ON THE MOTOR ACTIVITY OF A REHABILITATED PERSON - Maksymiak, V. M.; Kovalchuk, O. V. (Rehabilitation and Recreation, 2023)
The relevance of the study is due to the importance of rehabilitation in the life of a person who is undergoing a long recovery process. At the same time, more and more attention is now being paid to general physical training classes as an effective means of rehabilitation. In addition, it can be noted that general physical training is important during the development of motor activity, because in current realities, every patient wants to return to professional activities as soon as possible. It is also possible to note a significant increase in the number of programs for rehabilitation by means of general physical training. It is worth noting that the issue of general physical training is now considered also in the aspect of improving the emotional and psychological state of a person undergoing rehabilitation. In particular, a person whose motor activity increases feels joy and moral elation, because he understands that his recovery is successful. Therefore, currently, successful rehabilitation is mainly associated with motor activity, which is achieved by performing general physical training exercises. The goal is to theoretically and practically reveal the influence of general physical training classes on the motor activity of a rehabilitated person. Material. The material of the study is an experiment related to the effect of general physical training on the motor activity of a rehabilitated person, where the respondents of the experiment were 5 military personnel aged 25–29, who are undergoing rehabilitation after gunshot wounds of the lower and/or upper extremities. The study was conducted on the basis of real indicators of patients before and after the introduction of general physical training classes. The results. The conducted research made it possible to reveal the main aspects of the impact of general physical training classes on the motor activity of a rehabilitated person. The essence of the concept of «rehabilitation» is described. The main areas of rehabilitation are characterized. The characteristics of rehabilitation are determined. Types of classes based on the nature of general physical training exercises to improve motor activity were analyzed. The essence of the conducted research on the impact of general physical training classes on the motor activity of a rehabilitated person has been revealed. Special attention is paid to the results of the study, which were aimed at identifying the positive effect of exercises on persons undergoing rehabilitation due to gunshot injuries of the upper and/or lower extremities. It was determined that the conducted experiment revealed a significant potential of physical training, which contributes to the improvement of motor activity of the rehabilitated.